Optimalisasi Produktivitas Petani Jagung melalui Pelatihan Pembuatan Briket Janggel Berkemasan Inovatif - Rohmah, Lailiyatur; Dzulkarnain, M.; Solikhah, Nikmatus; Hardianti, Sela; Arrayan, Jasmine; Prameswari, Dhea Adelia; Wulandari, Diana; Arifin, Muhammad Saiful; Morale, Junta Teduh; Firmansyah, Meyra Tabitha Ariestia; Timamah, Maulidatus Syahrit; Saputra, Micky Yulio; Azizah, Zakiatul (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2025)
One of the main agricultural products in Ampel Village, Wuluhan Subdistrict, Jember Regency, is maize; therefore, corn cobs are abundantly available. This condition indicates strong potential for developing environmentally friendly, high-value charcoal briquettes. This community service program aims to enhance farmers’ skills in producing corn cob briquettes independently, provide affordable, environmentally friendly alternative energy sources, improve understanding of innovative packaging to increase product value, and create new business opportunities based on local agricultural waste. This program employs an Asset-Based Community Development (ABCD) approach, focusing on the utilization of local assets and potentials in Ampel Village. The corn cob briquette training improved farmers’ knowledge and skills in processing agricultural waste into high-quality briquettes with innovative packaging. The program opens new business opportunities, reduces dependence on conventional fuels such as LPG or kerosene, and supports sustainable development, although it still faces challenges related to seasonal raw material availability, product quality, and market access. Keywords: Farmer Productivity, Corn Cob Briquettes, Innovative Packaging Salah satu hasil pertanian di Desa Ampel Kecamatan Wuluhan Kabupaten Jember adalah jagung, sehingga bonggol jagung di desa ini melimpah. Realitas ini membuat menunjukkan potensi besar dalam pengembangan arang briket yang ramah lingkungan dan bernilai guna tinggi. Pengabdian ini bertujuan meningkatkan keterampilan petani dalam memproduksi briket bonggol jagung secara mandiri, menyediakan alternatif energi murah dan ramah lingkungan, meningkatkan pemahaman tentang kemasan inovatif untuk nilai jual, serta membuka peluang usaha baru berbasis limbah pertanian lokal. Penelitian ini menggunakan pendekatan Asset Based Community Development (ABCD) yang berfokus pada pemanfaatan asset dan potensi masyarakat Desa Ampel. Pelatihan briket janggel jagung di Desa Ampel meningkatkan pengetahuan dan keterampilan petani dalam mengolah limbah menjadi briket berkualitas dengan kemasan inovatif. Program ini membuka peluang usaha, mengurangi ketergantungan terhadap bahan bakar konvensional seperti LPG atau minyak, dan mendukung pembangunan berkelanjutan, meski masih menghadapi tantangan bahan baku musiman, kualitas produk, dan akses pasar. Kata kunci: Produktivitas Petani, Briket Janggel Jagung, Kemasan Inovatif